(untitled) (Albayan Scientific Journal, 2023)
The metabolic syndrome (MetS) is a major public-health challenges worldwide. MetS is defined by different health organization as a pathologic condition characterized by abdominal obesity, insulin resistance, hypertension, and hyperlipidemia. Central adiposity is a key feature of the metabolic syndrome, as reflected by the strong relationship between the prevalence of the metabolic syndrome and waist circumference (WC). The aims of this project are to review the components of metabolic syndrome and to review the literature describing the potential for antipsychotic medications to cause weight gain, hyperlipidemia and glucose dysregulation which are the components of metabolic syndrome. Antipsychotics drugs have been found to be strongly associated with weight gain, insulin resistance/glucose intolerance and dyslipidemia. Additionally, patients on antipsychotic drugs with metabolic syndrome are at high risk to develop type 2 diabetes and cardiovascular diseases. Most of the reviewed articles showed that atypical antipsychotics are with higher risk to develop metabolic syndrome than typical antipsychotics. It has been found that clozapine and olanzapine cause the highest significant changes in weight gain, glucose intolerance, dyslipidemia and their complications. Further, the risk of type 2 diabetes is higher in patient’s taking atypical antipsychotics (specifically; olanzapin&clozapine) than in those taking typical drugs.